Making Development Financing in LDCs More Conducive to Development - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
Making development financing in LDCs more conducive to development should be a priority for the next Programme of Action of the Istanbul Conference. It needs to go beyond the old and emblematic target of ODA to LDCs, which is too far to be reached. The present paper examines four issues.
Keywords: F35; O11; O19; 330; APD; PMA